Digitalization of Educational Administration in the Society 5.0 Era: An Islamic Work Ethics Perspective on Data Integrity and Managerial Efficiency - M. Habil Al-Faqih; Humaida; Latifah Nur Aprilyani; Asaranum Sila Safitri; Muhammad Lukman Adha; Nayla Alwiyatuzzahra; Adinata Rusmen Idris (Educatia : Jurnal Pendidikan dan Agama Islam, 2026)
The society 5.0 era drives digital transformation in educational administration, promising increased managerial efficiency but simultaneously raising threats of cybersecurity vulnerabilities and massive data breaches caused by human error. This study aims to systematically evaluate the extent to which the implementation of Islamic Work Ethics can secure data integrity while promoting managerial efficiency in educational environments. The method used is a Systematic Literature Review adopting comprehensive literature screening guidelines, followed by a thematic analysis approach to various academic sources from the last ten years. Research findings indicate that digitalization successfully reduces administrative bureaucracy obstacles. However, the lack of security literacy amplifies the risk of data privacy violations. The implementation of Islamic Work Ethics pillars, which include the values of honesty, accountability, adaptive intelligence, work precision, and justice, is proven to be a robust internal moral control instrument. The novelty of this study lies in the conceptualization of Islamic Work Ethics, positioning it not merely as a normative moral guideline, but transforming it into a 'spiritual firewall' that proactively patches the vulnerabilities of conventional IT governance. In conclusion, the advancement of technological systems is inadequate without being balanced by the ethical transformation of human resources. Institutional governance must integrate technological defense with spiritual resilience to actualize an efficient, transparent administration with high information security integrity.